Pre-service Elementary Generalist Teachers: Developing Competencies to Teach Visual Arts through the Studio Habits of Mind as a stance and artistic disposition - Tandon, Shruti (The Canadian Art Teacher / Enseigner les arts au Canada)

(untitled) (Canadian Society for Education through Art / Société canadienne d’éducation par l’art, 2024)
This qualitative case study investigates the development of perceived competency for teaching visual art in pre-service generalist teachers and their readiness to use visual arts in their future elementary classrooms through a visual art methodology course. Pre-service generalist teachers’ feelings of preparedness and sense of efficacy are both important indicators of whether they will be able to meet the challenges of incorporating visual arts in their future classrooms and as effective 21st century educators. To achieve this aim, the study considered in-depth firsthand experiences of four pre-service teachers and their course instructor for the entire semester during their training. The uncertainty of understanding the role of visual arts in contemporary education, lack of personal confidence, and prior negative experience in visual arts are some of the contributing fear factors. Scholars suggest that this thinking can be changed through appropriate experiences, influences and environments provided during the pre-service training stage. Findings illustrate that pre-service teachers indicated an optimistic shift in their confidence to pursue visual arts with a refreshed mindset, by applying the Studio Habits of Mind within learning and teaching visual arts.